Observatories: a tool for the social, cooperative, and solidarity sector in the region of Tolima, Colombia - Rivera González, Miguel Ángel; Rubiano Aranzales, Edicson (Cooperativismo & Desarrollo, 2016)
Purpose: This article seeks to give an account of an observatory as a tool for the social, cooperative, and solidarity sector in the department of Tolima, Colombia. Description: The observatory was created as a tool for the social, cooperative, and solidarity sector, taking into account that in the region of Tolima there are organizations that develop activities for collective or social benefit and whose sole purpose is to improve the living conditions of the collaborators or communities. These organizations and their activities led to the creation of the observatory, which advocates for continuous processes of education, training, technical as- sistance, and research. This is so that higher standards of cohesion, integration, coordination, visibility, productivity, competitiveness, innovation, and entrepreneurship may be attained. Viewpoint: The lack of information to make decisions and generate collective action is one of the factors preventing the work of organizations within and around particular environments from being recognized. Conclusions: While it is true that an observatory has many features, one must think of it in the context of a network where collaborative work is the cornerstone of construction based on aspects such as multiculturalism and a multidisciplinary approach.